Fluid‐Driven Soft CoboSkin for Safer Human–Robot Collaboration: Fabrication and Adaptation. (8th July 2020) - Heng, Wenzheng; Yang, Geng; Pang, Gaoyang; Ye, Zhiqiu; Lv, Honghao; Du, Juan; Zhao, Guodong; Pang, Zhibo
Abstract : In human–robot collaboration, the wrapping material on robots is not only required to have the sensing ability to adapt to the external environment but also need to have the function of cushioning the collision between human and robot. Herein, a fluid‐driven soft robot skin with sensing and actuating function is successfully applied to a collaborative robot and working well with the host robot. The skin is an integration of sponge force sensors and pneumatic actuators. By altering the internal air pressure in pneumatic actuators, the developed robot skin can provide more than ten times tunable stiffness and sensitivity. In addition, the skin can reduce the peak force of the collision and achieve the actuating function. Using three‐dimensional printing and computer‐aided design, the skin is fabricated and attached to a collaborative robot conformally. Drawing upon the data acquisition and control system, the experiment for illustrating the applications of the CoboSkin is successfully performed. The skin provides the robot with multi‐functions, which are similar to the human muscle and skin attached to human bones. By mimicking human skin and muscle with tactile sensing function and stiffness tuning function, CoboSkin can enhance the adaptability of the robot to human daily life. Abstract : To enhance the safety of human–robot collaboration, both information perception and soft cushioning abilities are required. Herein, a novel device integrated with sensors and actuators, providing active sensing and cushioning actuating functions, is presented for human–robot collaboration.